Resposta objetiva tumoral e taxas de sobrevida de pacientes com cirrose e carcinoma hepatocelular submetidos à radioembolização com ¹³¹I-lipiodol versus quimioembolização arterial - Ribeiro, Michele Costa de Oliveira [UNESP] (2023)
Introduction: Hepatocellular carcinoma (HCC) occurs mainly in the presence of cirrhosis and its treatment involves therapies such as transarterial chemoembolization (TACE), which is the most used nonsurgical therapy. However, the risk of complications associated with TACE is higher in cases of portal vein thrombosis (PVT), a finding that is not rare in HCC. Transarterial radioembolization (TARE) can be performed in the presence of PVT, but TARE with ¹³¹I-lipiodol was not sufficiently assessed in these cases. Objective: To compare the effectiveness of TACE and TARE with ¹³¹I-lipiodol regarding objective tumor reduction, measured through volumetric analysis of HCC images before and after the procedures. Methods: We evaluated 32 patients with HCC randomized to receive TACE or TARE with ¹³¹I-lipiodol. Locoregional response and survival rates were compared between the treatments. Results: 37 tumors were evaluated (19 received TACE and 18 received TARE with ¹³¹I-lipiodol, of which seven were associated with PVT). The median tumor reduction ranged from 37.6 to 47.3%, with no significant difference between the groups (p= 0.494) and regardless the PVT presence. The mean survival was 345 days, with no significant difference between groups (p= 0.656). However, mean survival in PVT cases was 196 days, which was lower than observed without PVT (p= 0.010). Conclusions: Both treatments promoted significant tumor reduction, showing that TARE with ¹³¹I-lipiodol is effective not only in cases without PVT, but also for those with this complication. These results suggest that TARE with ¹³¹I-lipiodol should be part of the HCC treatment, thus making locoregional therapy available for patients with PVT.